2008
DOI: 10.1002/ldr.875
|View full text |Cite
|
Sign up to set email alerts
|

The effect of natural zeolites and organic fertilisers on the characteristics of degraded soils and yield of crops grown in Western Serbia

Abstract: Soils with unfavourable characteristics (pronounced acidity, disturbed structure, compaction, exhaustion, tiredness, etc.) cover a considerable area of Serbia. Specific crops, the fruit ones in particular, are being grown on these soils, yielding, however, considerably lower yields. The paper presents results of two-year studies on the effect of natural zeolites, organic fertilisercattle manure and mineral NPK fertiliser (15:15:15) on soil properties and fruit yield and fruit properties of strawberry and black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
(17 reference statements)
1
17
0
1
Order By: Relevance
“…Jelic et al (2006) reported that mineral fertilization, primarily with large K and N TOT rates applied to the vertisol undergoing degradation, caused a substantial increase in acidity (0.29 to 0.37 pH units in active acidity and 0.18 to 0.24 units in substitutionary acidity), humus, N TOT and available P and K in the soil. Glisic et al (2009) A, B -'Cultivar' and 'Fertilizer' treatment; letter(s) in vertical columns indicate a significant difference between means at *P < 0.05 and **P < 0.01 by LSD test; ns -non-significant difference rates of complex NPK fertilizers broadcast annually across the rows in pear, blackberry and strawberry plantings, induced disturbances in mineral nutrition, primarily due to the accumulation of higher amounts of K and increases in the soil acidity. The results of the above authors were confirmed by the results of the present study.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Jelic et al (2006) reported that mineral fertilization, primarily with large K and N TOT rates applied to the vertisol undergoing degradation, caused a substantial increase in acidity (0.29 to 0.37 pH units in active acidity and 0.18 to 0.24 units in substitutionary acidity), humus, N TOT and available P and K in the soil. Glisic et al (2009) A, B -'Cultivar' and 'Fertilizer' treatment; letter(s) in vertical columns indicate a significant difference between means at *P < 0.05 and **P < 0.01 by LSD test; ns -non-significant difference rates of complex NPK fertilizers broadcast annually across the rows in pear, blackberry and strawberry plantings, induced disturbances in mineral nutrition, primarily due to the accumulation of higher amounts of K and increases in the soil acidity. The results of the above authors were confirmed by the results of the present study.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%
“…Given the average organic matter content of 25.0% in composted beef manure (DeLuca and DeLuca 1997), the reaction was as expected and in line with the results of the cited authors. Apart from increasing the humus content of soil, cattle manure had a favourable effect through decreasing acidity due to the significant proportion of H 2 CO 3 reacting with the soil adsorption complex (Glisic et al 2009). This results in the formation of NaHCO 3 , which in an aqueous solution, breaking down into weak non-dissociating H 2 CO 3 and strong dissociating NaOH, with several OH -ions occurring in the soil, thus resulting in an acidity decrease (Chander and Joergensen 2002).…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%
“…Cattle manure had a favourable effect through decreasing acidity due to the significant proportion of H 2 CO 3 reacting with the soil adsorption complex [34].…”
Section: Animal Manurementioning
confidence: 99%
“…According to Kwiatkowska and Maciejewska (2008), the introduction of carbon into soil contributes to the improvement of soil properties due to an increase in soil reaction and cation exchange capacity, and a reduction of hydrolytic acidity. The positive effect of zeolite on soil properties is confirmed in research by Glisic et al (2009) and Jayasinghe et al (2010). CONCLUSIONS 1.…”
mentioning
confidence: 64%